The efficiency of interferon stimulated gene 15 expression in peripheral blood for early pregnancy prediction in Awassi ewes - Eman H. Lazim; Khawla A. Hussein; Dhafer M. Aziz (Iraqi Journal of Veterinary Sciences)
This study was designed to identify the efficiency of interferon-stimulated gene 15 (ISG15) expression for early pregnancy detection in Awassi ewes. A total of 10 ewes were enrolled: 3 carrying twins, 4 carrying single pregnancies, and 3 non-pregnant. Blood samples were collected on 0, 6, 15, and 25 days of gestation to measure ISG15 expression levels using quantitative real-time PCR (qRT-PCR). The results of the relative expression values of ISG15 in pregnant and non-pregnant ewes on 0, 6, 15, and 25 days of pregnancy were 0.044±0.012 vs. 0.049±0.009, 0.203±0.083 vs. 0.201±0.093, 1.839±0.594 vs. 0.292±0.136, and 0.583±0.067 vs 0.200±0.051, respectively. In both twin and single pregnant ewes, the relative expression values of ISG15 were increased significantly (P<0.05) on 15 day of pregnancy, after that the values declined significantly (P<0.05) on day 25. No significant differences in ISG15 expression were observed between ewes carrying twins and those carrying single fetuses. Receiver operating characteristic (ROC) curve analysis showed that the area under the curve (AUC) on days 0 and 6 of pregnancy was 0.405, whereas on days 15 and 25 it was 0.952 and 1.00, respectively. The accuracy, specificity, sensitivity, and positive and negative predictive values of ISG15 expression on days 15 and 25 of pregnancy were 90%, 100%, 85.7%, 100%, and 75%, and 100%, 100%, 100%, 100%, and 100%, respectively. In conclusion, ISG15 expression demonstrated high accuracy as an early pregnancy marker in Awassi ewes, with greater diagnostic reliability on day 25 compared to day 15 of gestation.